2011
DOI: 10.1063/1.3579191
|View full text |Cite
|
Sign up to set email alerts
|

Optical trapping of synaptic vesicles in neurons

Abstract: We demonstrate intracellular manipulation of synaptic vesicles in living neurons by optical trapping. When an infrared trapping laser is focused on synapses of a neuronal cell labeled with a fluorescent endocytic marker, fluorescence is observed at the focal spot. The fluorescence spectrum is attributed to fluorescent dye in the synaptic vesicles, indicating excitation by two-photon absorption of the trapping laser. The fluorescence intensity increases gradually within ∼100 s of laser irradiation, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…We have demonstrated that the tangle protein and molecular motor can be trapped and transported/received into the optical waveguide by optical tweezers (Hosokawa et al 2011, Mthunzi et al 2010. By utilizing the specific optical pulse input power, the dynamic tweezers can be generated to transport, store, and deliver the molecule volumes to their final destination via the molecular buffer and bus network.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We have demonstrated that the tangle protein and molecular motor can be trapped and transported/received into the optical waveguide by optical tweezers (Hosokawa et al 2011, Mthunzi et al 2010. By utilizing the specific optical pulse input power, the dynamic tweezers can be generated to transport, store, and deliver the molecule volumes to their final destination via the molecular buffer and bus network.…”
Section: Resultsmentioning
confidence: 97%
“…Hosokawa et al (Hosokawa et al 2011) demonstrated the optical trapping of synaptic vesicles in a hippocampal neuron and found that the intracellular synaptic vesicles can be trapped at the focal spot within the laser irradiation time because the vesicles form clusters in a neuron. These clusters can effectively trap at the focal spot because of high polarizability.…”
Section: Principle and Methodsmentioning
confidence: 97%
“…2(a)), which was attributed to two-photon fluorescence intensity of FM1-43 dyes excited by the trapping laser. The fluorescence intensity at the focal spot increased gradually with the laser irradiation time, suggesting that optical trapping force causes vesicles assembly at the laser focus [9]. We investigated synaptic vesicle dynamics in an optical trap by FCS.…”
Section: Resultsmentioning
confidence: 98%
“…1(b) [9]. Briefly, a 1064-nm near-infrared (NIR) laser beam from a continuous wave YVO 4 laser (Spectra Physics) was used for optical trapping and two-photon excitation light source.…”
Section: Methodsmentioning
confidence: 99%
“…Living cells and important biological applications can be investigated using optical tweezers. 40 Hosokawa et al 41 have demonstrated the optical trapping of synaptic vesicles in a hippocampal neuron and found that the intracellular synaptic vesicles can be trapped at the focal spot within the laser irradiation time. This occurs because the vesicles form clusters in neurons, and are effectively trapped at the focal spot due to its high polarizability.…”
Section: Alzheimer's Diagnosis Using Molecular Networkmentioning
confidence: 99%